2004
DOI: 10.1111/j.1365-2311.2004.0590.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeny revisited: condensed tannins as anti‐herbivore defences in leaf‐chewing herbivore communities of Quercus

Abstract: Abstract.  1. Community level oak–tannin–insect patterns have been largely unexplored since Paul Feeny's ground‐breaking research. Two hypotheses were tested for Quercus velutina and Q. alba in the Missouri Ozarks: abundance and richness of leaf‐chewing herbivores are negatively correlated with foliar condensed tannin concentrations and variation in condensed tannin concentrations explains variation in herbivore community structure. 2. In 2001, foliar condensed tannins in the understorey and canopy of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
197
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(210 citation statements)
references
References 90 publications
10
197
3
Order By: Relevance
“…tree neighboring our study site. The aforementioned record by Briceño (1989) and this confi rming observation lends additional support to our hypothesis, since some Inga species are known for their high contents in condensed tannins (Koptur 1985, Galindo et al 1989, Myster 2002), a group of compounds commonly known as defensive, due to their alleged antinutritional properties (Balick et al 1978, Tempel 1981, Forkner et al 2004.…”
supporting
confidence: 70%
“…tree neighboring our study site. The aforementioned record by Briceño (1989) and this confi rming observation lends additional support to our hypothesis, since some Inga species are known for their high contents in condensed tannins (Koptur 1985, Galindo et al 1989, Myster 2002), a group of compounds commonly known as defensive, due to their alleged antinutritional properties (Balick et al 1978, Tempel 1981, Forkner et al 2004.…”
supporting
confidence: 70%
“…Larvae fed on late-gathered leaves encountered the accumulation of host defences as those leaves matured and produced very small pupae that had zero survival to adulthood. Subsequent authors have studied changes of leaf quality over shorter time periods and confirmed that the rapid decline of host quality as leaves mature reduces the pupal weight of late-feeding insects (Wint 1983;Buse et al 1999;Forkner et al 2004;van Asch & Visser 2007). Small pupae pay a clear penalty in terms of fecundity (figure 5).…”
Section: Fecundity -Mortality Trade-offs As Drivers Of Asynchronymentioning
confidence: 99%
“…Factors infl uencing both food availability and resistance against herbivores such as seasonality ( Shure and Wilson, 1993 ;Coley, 1998 ;Forkner et al, 2004 ;Pearse and Hipp, 2012 ;Scherrer et al, 2016 ), habitat structure (which governs the eff ects of the microclimate or spatial distribution of the host plants) ( Nice and Fordyce, 2006 ;Stoepler and Lill, 2013 ) and the natural history of plants (i.e., life forms) ( Th ompson, 1988 ;Menge, 2003 ), are therefore likely to promote temporal and spatial variation in plant-herbivore network parameters. In this study, we investigated the infl uence of foliar resistance traits and plant cover on species-level parameters of plant-herbivore networks, specifi cally on plant species strength (i.e., how important a plant species is to a set of herbivores) and herbivore selectiveness (herbivore specialization).…”
Section: A M E R I C a N J O U R N A L O F B O T A N Y R E S E A R C mentioning
confidence: 99%